THE RAN IMAGE METHOD: EXPLORING THE SCIENTIFIC APPROACH IN FINE ARTS - I. Mamatov (Galaxy International Interdisciplinary Research Journal, 2023)
The incorporation of scientific methodologies in the field of fine arts has revolutionized the way we approach and understand various artistic forms. This article aims to delve into a specific scientific technique known as the Ran Image Method, which has been widely employed for working with the image of a person in the realm of fine arts. By examining the origins, processes, and applications of this method, we will unravel the intricate relationship between science and artistry, shedding light on the innovative ways in which artists capture and interpret the essence of human subjects.